Georgia Architectural and Historic Properties Survey of Rural [016] East section of the county, Brooks, Ga. December 1980 - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Rural [016] East section of the county, Brooks, Ga. December 1980. A one story rectangular plan with gabled tin roof and clapboard siding. Shed porch with tapered square posts (screened). Sash windows with 4/4 lights. Exterior chimney. Brick piers. Good condition. Date of Construction: c. 1910. A typical vernacular farmhouse common to these rural areas.
A one story rectangular plan with gabled tin roof and clapboard siding. 1 electronic record and assets. Digitized from originals. 1 PDF. 1 scan. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 948 KB (971,474 bytes).
Keywords: Historic buildings; Real property surveys; Brooks County (Ga.); Lowndes County Historical Society (Lowndes County, Ga.); Quitman (Ga.)